MEDIA ATLAS MORFOLOGI DAN ANATOMI DAUN TANAMAN HIAS MONOKOTIL - Minati, Minati; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Atlas morphological and anatomical leaves of monocotyl ornamentalplants contained morphological images and leaf anatomy that are usedas learning media to facilitate students to understand the structure andfunction tissue plant of class XI. This study aims to compile andvalidate atlas media. The research method is descriptive quantitative.The stages of making atlas media consist of preproduction, productionand post-production. The instruments used to validate are instrumentquestionnaires and media questionnaires consist of four aspects(presentation, content, language and use) and 21 items of assessmentcriteria. Instrument questionnaire was validated by two FKIP lecturersand media questionnaires validated by five validators (two lecturersand 3 class XI biology teachers) with a likert scale 1-4. Calculation ofmedia validity refers to Lawshe. The results of the instrumentvalidation show that it is suitable for use which means that the mediavalidation sheet can be used by the validator to assess the media. Thenthe atlas media obtained a CVI value of 0.96 from the four aspectsassessed. Aspects of presentation, language and use reached theminimum value but in the content aspects only reached 0.88 so that thecontent aspects need to be improved before being used in learning.